Characteristics of Islamic Religious Education in Boarding School Curriculum - Rumainur Rumainur; Umar Fauzan; Noor Malihah (Southeast Asian Journal of Islamic Education, 2022)
Boarding schools are Islamic educational institutions that have been proven and still survive with all of the dynamics until today. A characteristic that distinguishes boarding schools from others is the 24-hour educational system that supports character building. Additionally, the curriculum is developed to meet the needs, so it makes the boarding school more unique. This research aimed at describing the characteristics of Islamic Religious Education (PAI) courses in the boarding school curriculum. The research approach used was descriptive qualitative. The research location was Tahfidzul Qur’an Boarding School of Ahlus Shuffah Balikpapan. The primary data sources of this research were the management/ leader, educational division, asatidz (teachers) and student representatives. The data collection was through observation, interviews, and documentation. The data analysis techniques used data reduction, data display and verification. The results showed that PAI course at Tahfidzul Qur’an boarding school of Ahlus Shuffah Balikpapan was through maximizing the education in the classroom, in the mosque, in the dormitory, as well as in the real-life interaction. The boarding school does not only teach PAI knowledge or materials contained in the boarding school curriculum and in the co-curriculum, but also general knowledge and skills as a provision to take the equivalence examination at the Wustha (junior high) level or Ulya (senior high) level in order to get a diploma equivalent to MTs/SLTP or MA/SLTA at the Ministry of Religious Affairs. This research is expected to broaden the societies’ view that education at boarding school is highly appropriate, complete and provides a diploma that is legalized by the government.